Partisan tax policy and income inequality in the US, 1979 - 2007 - Olivier Bargain; Mathias Dolls; Herwig Immervoll; Dirk Neumann; Andreas Peichl; Nico Pestel; Sebastian Siegloch (Institute for the Study of Labor (IZA), 2013)
We assess the effects of U.S. tax policy reforms on inequality by applying a new decomposition method that allows us to disentangle the direct policy effect from the effect of changing market incomes. Over the whole period 1979-2007 the cumulative tax policy effect aggravated income inequality by increasing the income share of the top 20% in contrast to the middle class' share. The tax policy effect accounts for up to 29% of the total change in inequality; its contribution increases up to 41% if we take into account behavioral responses. Using our unique policy effect measure and variation in tax policies across U.S. states and time, we also identify the redistributive intention of policymakers. The estimated effect of partisan politics on the U.S. income distribution is statistically significant and economically important. Republican policymakers increased inequality especially at the top whereas Democrats increased the income share of the bottom 80% of the distribution.
Keywords: H23; H31; H53; P16; 330; tax policy; inequality; redistribution; partisan politics; political economy